Analisis peranan usaha kerajinan rumah tangga dalam rangka penyerapan tenaga kerja dan membangun masyarakat ekonomi kecil di Kabupaten Bantul - Susianti, Susianti (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to analyze the role of folk/household handicraft businesses in the context of employment and building a small economic community through the analysis of factors affecting the income of household craftsmen in the Bantul Regency. Problems that are still encountered in the household handicraft business are related to business activities carried out traditionally and the scale of business is still limited. So this has an impact on the amount of product produced is still limited, and indirectly the level of income is still low. To increase production efforts means the factors that support it are needed. Data sources used are primary data and secondary data. The quantitative analysis used is multiple regression analysis with the Ordinary Least Square (OLS) method. Based on the results of descriptive analysis, the main reason that encourages the craftsmen to run a household handicraft business in Bantul Regency is the main work to obtain and add income to meet their needs. And the household handicraft business plays a role in employment in Bantul Regency by 13.69%. Meanwhile, based on the regression results, the variable of business capital and raw materials have positive and significant coefficients. Where business capital is the variable that has the most influence on the income of craftsmen household crafts in Bantul Regency.